2021
DOI: 10.1021/acsomega.1c05362
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Bioactivity Assessment, and Molecular Docking of Non-sulfonamide Benzimidazole-Derived N-Acylhydrazone Scaffolds as Carbonic Anhydrase-II Inhibitors

Abstract: This research reports the synthesis of new benzimidazole-derived N -acylhydrazones (NAH), their characterization using various spectroscopic methods, and in vitro evaluation as potent carbonic anhydrase-II inhibitors. Among the target compounds ( 9–29 ), few showed higher inhibition than the standard acetazolamide (IC 50 : 18.6 ± 0.43 μM), for example, compound 9 (IC 50 : 13.3 ± 1.25 μM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This simple transformation is involved in a wide range of physiological processes (such as pH regulation, gas exchange, ion transport, bone resorption, fatty acid metabolism, etc.) [ 48 ]. In addition, CAs are associated with a plethora of pathological conditions, including glaucoma, edema, epilepsy, obesity, hypertension, cancer, neuropathic pain, and other neurological disorders [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…This simple transformation is involved in a wide range of physiological processes (such as pH regulation, gas exchange, ion transport, bone resorption, fatty acid metabolism, etc.) [ 48 ]. In addition, CAs are associated with a plethora of pathological conditions, including glaucoma, edema, epilepsy, obesity, hypertension, cancer, neuropathic pain, and other neurological disorders [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the new nonclassical CA inhibitors were focused on designs that did not contain either sulfamide or sulfonamide. It was mentioned previously that the conventional CA inhibitors are nonselective, that is why they can cause unexpected different inhibitors and side effects; moreover, a massive part of the population worldwide has an allergy to sulfamides or sulfonamides (Saadiq et al., 2021). Upon thorough examination of the interaction between sulfonamide/sulfanamide derivatives and CAs, it becomes apparent that a sulfamide or sulfonamide group is involved in coordinating the zinc cation within the catalytic domain of hCA.…”
Section: Resultsmentioning
confidence: 99%
“…The target compounds 7a–m were finally synthesized by refluxing the equimolar amounts of 5 with different aromatic aldehydes 6a–m for 4–6 h catalyzed using 3–5 drops of organic or mineral acids. 11 After completion, the product was precipitated in freezing water, filtered, washed, and dried. All the compounds were colored solids, having high melting points and soluble in polar solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has previously reported benzimidazole-based antioxidants (IC 50 : 131.50 ± 12.39; IC 50 : 167.4 ± 7.4), α-glucosidase (IC 50 : 352 μg/mL), cholinesterase (IC 50 : 121.2 μM and 38.3 μM), and carbonic anhydrase inhibitors (IC 50 : 13.3 ± 1.25 μM). 10 , 11 …”
Section: Introductionmentioning
confidence: 99%